Influence of Infill Structure Shape and Density on the Mechanical Properties of FDM 3D-Printed PETG and PETG+CF Materials - Hozdić, Emine; Hozdić, Elvis (Advanced Technologies and Materials, 2024)
This paper investigates the impact of infill structure shape and density on the mechanical properties of Fused Deposition Modelling (FDM) 3D-printed materials, specifically PETG and PETG reinforced with carbon fibers (PETG+CF). The research aims to optimize additive manufacturing processes by examining how different infill geometries—hexagonal, triangular, and linear—and varying infill densities (30%, 60%, and 100%) influence the mechanical strength, tensile properties, and flexibility of the printed components. Experimental tensile tests were conducted on specimens to assess key mechanical parameters including maximum force, break force, Young's modulus, tensile strength, and nominal strain at break. Results indicate that infill shape and density significantly affect the mechanical performance of 3D-printed materials. Hexagonal infill structures demonstrated superior mechanical properties, with a 45.11% increase in maxi-mum force compared to triangular infill structures. Additionally, increasing the infill density from 30% to 100% resulted in a 69.13% increase in maximum force and a 64.87% increase in break force for PETG+CF specimens. These findings provide valuable insights for enhancing the quality and performance of FDM 3D-printed products, offering guidelines for the development of advanced materials with tailored mechanical properties for various industrial applications.